Pharmacological interventions for agitation in patients with traumatic brain injury: protocol for a systematic review and meta-analysis. Issue 1 (December 2016) - Williamson, David; Frenette, Anne; Burry, Lisa; Perreault, Marc; Charbonney, Emmanuel; Lamontagne, François; Potvin, Marie-Julie; Giguère, Jean-François; Mehta, Sangeeta; Bernard, Francis
Abstract Background Traumatic brain injury (TBI) is a worldwide leading cause of mortality and disability. Among TBI complications, agitation is a frequent behavioural problem. Agitation causes potential harm to patients and caregivers, interferes with treatments, leads to unnecessary chemical and physical restraints, increases hospital length of stay, delays rehabilitation, and impedes functional independence. Pharmacological treatments are often considered for agitation management following TBI. Several types of agents have been proposed for the treatment of agitation. However, the benefit and safety of these agents in TBI patients as well as their differential effects and interactions are uncertain. In addition, animal studies and observational studies have suggested impaired cognitive function with the use of certain antipsychotics and benzodiazepines. Hence, a safe and effective treatment for agitation, which does not interfere with neurological recovery, remains to be identified. Methods/design With the help of Health Sciences librarian, we will design a search strategy in the following databases: PubMed, Ovid MEDLINE®, EMBASE, CINAHL, PsycINFO, Cochrane Library, Google Scholar, Directory of Open Access Journals, LILACS, Web of Science, and Prospero. A grey literature search will be performed using the resources suggested in CADTH'sGrey Matters . We will include all randomized controlled, quasi-experimental, and observational studies with control groups. The population of interest is all patients, including children and adults, who have suffered a TBI. We will include studies in which agitation, not further defined, was the presenting symptom or one of the presenting symptoms. We will also include studies where agitation was not the presenting symptom but was measured as an outcome variable and studies assessing the safety of these pharmacological interventions in TBI patients. We will include studies evaluating all pharmacological interventions including beta-adrenergic blockers, typical and atypical antipsychotics, anticonvulsants, dopamine agonists, psychostimulants, antidepressants, alpha-2-adrenergic agonists, hypnotics, and anxiolytics. Discussion Although agitation is frequent following TBI and pharmacological agents that are often used, there is no consensus on the most efficacious and safest strategy to treat these complications. There is a need for an updated systematic review to summarize the evidence in order to inform practice and future research. Systematic review registration PROSPEROCRD42016033140